EEG-based Emotion Recognition Using Self-Organizing Map for Boundary Detection - Khosrowabadi, Reza; Hiok Chai Quek; Wahab, Abdul; Kai Keng Ang (2010 20th International Conference on Pattern Recognition, 2010)
This paper presents an EEG-based emotion recognition system using self-organizing map for boundary detection. Features from EEG signals are classified by considering the subjects' emotional responses using scores from SAM questionnaire. The selection of appropriate threshold levels for arousal and valence is critical to the performance of the recognition system. Therefore, this paper investigates the performance of a proposed EEG-based emotion recognition system that employed self-organizing map to identify the boundaries between separable regions. A study was performed to collect 8 channels of EEG data from 26 healthy right-handed subjects in experiencing 4 emotional states while exposed to audio-visual emotional stimuli. EEG features were extracted using the magnitude squared coherence of the EEG signals. The boundaries of the EEG features were then extracted using SOM. 5-fold cross-validation was then performed using the k-nn classifier. The results showed that proposed method improved the accuracies to 84.5%.